Bicomponent supramolecular self‐assemblies studied with tip‐enhanced Raman spectroscopy. (22nd September 2020) - Jiang, Song; Zhang, Rui; Zhang, Xian‐Biao; Zhang, Yang; Zhang, Yao; Dong, Zhen‐Chao
Abstract: The formation of well‐ordered supramolecular self‐assembly based on cytosine and 4, 4′‐bipyridine on Ag(111) has been investigated with subnanometer‐resolved tip‐enhanced Raman spectroscopy (TERS) using a low‐temperature ultrahigh‐vacuum scanning tunneling microscope (STM). The co‐deposition of two molecules on the Ag(111) surface held at room temperature results in well‐ordered hydrogen‐bonded monolayer islands, which transform into well‐aligned double‐stranded chains after thermal annealing. Site‐dependent TERS spectra help to identify the packing structures of molecular assemblies. The changes of molecule‐specific vibrational fingerprints across the assemblies can be clearly monitored by combining high‐resolution TERS spectra with advanced multivariate analysis. Furthermore, the peak positions and relative intensities for characteristic vibrational modes of the two molecules are found to vary due to the changes of the local hydrogen bonding and interaction environment in different molecular samples. Our findings demonstrate that TERS is sensitive to the local molecular interactions, provides new potentials to monitor the functionality of molecular architectures on demand, and opens new opportunities to probe surface chemistry at the nanoscale. Abstract : The co‐deposited samples of cytosine and 4, 4′‐bipyridine on Ag(111) were investigated with tip‐enhanced Raman spectroscopy before and after thermal annealing. Variations in peak positions and relative intensities for specific Raman modes are used to probe the changes of local interaction environments in different samples, particularly regarding hydrogen bonding and interactions with surface ad‐atoms.